Infância, ludicidade e pedagogia hospitalar: encontros e desencontros nas práticas educativas - Rodrigues, Maria Carolina Canale Sanches [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The aim of this study is to investigate the significance of educational practices aimed at children in non formal education, in this case, specifically, the hospital context. The chosen methodology is part of an investigation conducted in two phases. In the first phase was carried out a theoretical stage, scientifically based studies guided by an historical-cultural and Sociology of Childhood, enabling placement on the particularities of children, the playfulness and the positioning of Pedagogy in the hospital. After this theoretical study was performed the second phase, with the completion of an empirical study with a research and intervention in a hospital playroom, in a public hospital considered a regional center in the northwestern city of São Paulo. The methodological procedures adopted for this empirical study were participant observation, interviews, action research and a questionnaire. Participant observation and action research are conducted within the brinquetodeca in five meetings with about 15 children, interviews were conducted with three family members and the questionnaire was applied to a healthcare professional. Among the results we can mention the following findings: a confirmation of the necessity of work in the hospital directing playful adaptations for the preservation and development of children's learning, and recent publications are scarce about the Hospital Education and underscore the need for the professional practice of education in non-school, the educational activities carried out reveals the possibilities of offering the child the continuation of their educational activities involving the playful and educational, the international and national literature on educational practices in the hospital allow to check ...(Complete abstract click electronic access below)

hospitalar, em um Hospital Público considerado referência regional em uma cidade do noroeste paulista. Os procedimentos metodológicos adotados para este estudo empírico foram a observação participante, a entrevista, a pesquisa-ação e um questionário. A observação participante e pesquisa-ação foram realizadas dentro da brinquetodeca, em cinco encontros com aproximadamente 15 crianças, as entrevistas foram realizadas com 3 familiares e o questionário foi aplicado a um profissional da área da saúde. Dentre os principais resultados podemos mencionar as seguintes constatações: a confirmação da necessidade do trabalho lúdico no contexto hospitalar direcionando adequações para a preservação do desenvolvimento e aprendizagem infantil; as publicações são recentes e escassas acerca da Pedagogia Hospitalar e reforçam a necessidade da atuação do profissional da educação em contexto não-escolares; as atividades pedagógicas realizadas revelam as possibilidades de oferecer à criança a continuação de suas atividades educativas, envolvendo o lúdico e o pedagógico; a bibliografia nacional e internacional sobre as práticas educativas na instituição hospitalar permitem averiguar que o trabalho pedagógico em hospitais apresenta diversas interfaces de atuação: intervenção, estimulação, escolarização, pesquisa e principalmente o voluntariado. Em suma concluímos que a Pedagogia Hospitalar constitui-se de fato em um campo viável e adequado para o enfrentamento da hospitalização e da preservação da infância e pode ser ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Infância; Ludicidade; Pedagogia hospitalar; Childhood; Playfulness; Pedagogy Hospital